Laparoscopic Common Bile Duct Exploration Four-Task Training Model: Construct Validity - Sánchez, Alexis (Society of Laparoendoscopic Surgeons, 2012)
BACKGROUND: Training models in laparoscopic surgery allow the surgical team to practice procedures in a safe environment. We have proposed the use of a 4-task, low-cost inert model to practice critical steps of laparoscopic common bile duct exploration. METHODS: The performance of 3 groups with different levels of expertise in laparoscopic surgery, novices (A), intermediates (B), and experts (C), was evaluated using a low-cost inert model in the following tasks: (1) intraoperative cholangiography catheter insertion, (2) transcystic exploration, (3) T-tube placement, and (4) choledochoscope management. Kruskal-Wallis and Mann-Whitney tests were used to identify differences among the groups. RESULTS: A total of 14 individuals were evaluated: 5 novices (A), 5 intermediates (B), and 4 experts (C). The results involving intraoperative cholangiography catheter insertion were similar among the 3 groups. As for the other tasks, the expert had better results than the other 2, in which no significant differences occurred. The proposed model is able to discriminate among individuals with different levels of expertise, indicating that the abilities that the model evaluates are relevant in the surgeon's performance in CBD exploration. CONCLUSIONS: Construct validity for tasks 2 and 3 was demonstrated. However, task 1 was no capable of distinguishing between groups, and task 4 was not statistically validated.